Uji Korelasi dan Analisis Lintas Terhadap Karakter Agronomi dan Hasil Pada Galur-Galur Sorgum (Sorghum bicolor L.) - Dewi Andriani; Desta Wirnas; Trikosoemaningtyas Trikosoemaningtyas; Jekki Irawan; Jasmi Jasmi (Universitas Teuku Umar, 2023)
Correlation test and path analysis aims to obtain agronomic characters and yields that can be used as selection criteria for sorghum lines. The research design used was an augmented design with treatment of 60 F6 sorghum lines without repetition. Correlation test results in this research showed that the characters of plant height, stem diameter, number of leaves, panicle length, panicle diameter and panicle weight had a positive and significant correlation to sorghum yields. The path analysis results showed that panicle weight has a high value of direct effect on yield, while plant height, stem diameter, number of leaves, panicle length, panicle diameter has an indirect effect on yield. Agronomic characters and yields that can be recommended as selection criteria are plant height, stem diameter, number of leaves, panicle length, panicle diameter and panicle weight.